Epigonus okamotoi (Perciformes: Epigonidae), a junior synonym of E. draco, with new distributional records for E. atherinoides and E. lifouensis in the West Pacific - Okamoto, Makoto; Chen, Wei-Jen; Shinohara, Gento (Zootaxa, 2018)
Epigonus okamotoi Fricke, 2017 was originally described on the basis of a single specimen collected from New Britain, Papua New Guinea during one of the exploratory cruises (campaign: MADEEP) in 2014 organized under the Tropical Deep-Sea Benthos program. However, there are no clear differences in the meristic and morphometric characters between the holotype of the new species and specimens of E. draco Okamoto, 2015, including two additional specimens of the species found in the ichthyological collections in the NTUM. The genetic distance (p-distance) between the two “species” at the COI locus was negligible. Accordingly, the holotype of E. okamotoi is considered to be a specimen of E. draco, and the former nominal species is reduced to a junior synonym of E. draco. In addition, we rediagnose and report new distributional records for E. atherinoides (Gilbert, 1905) and E. lifouensis Okamoto & Motomura, 2013 in the West Pacific.